Study on the properties of natural rubber latex reinforced by polystyrene resin emulsion - Haisheng Tan; Yingping He (Proceedings of IRRDB Symposium 1999, Hainan, Peoples Republic of China. pp.437-450., 1999)
The effects of different preparation technology and proportion of PS to NR on the natural rubber latexs vulcanized rubber films mechanical properties, the reinforced NR latexs colloid property, rubber film-forming property and its vulcanized rubber films solvent resistance and ageing resistance were investigated. Relative Reinforced Degree (RRD) is characterized the reinforced effect of NR latex. The results show that: PS emulsion can reinforce NR latex effectively; The reinforced NR latex which uses in situ polymerizing technology overcomes thickening phenomenon which is very easy to be caused by pre-polymerizing and blending technology; the reinforced NR latex still have very good film-forming effect; the solvent resistance and ageing resistance of the reinforced vulcanized rubber film are improved, and the age-resisting property of the vulcanized rubber film using in situ polymerizing technology is worse than that of using pre-polymerizing and blending. The adherent way of PS resin R were studied by means of extraction.
Keywords: Emulsion polymerization; NR latex; Reinforcement; Styrene